(untitled) (International Journal of Nursing Education, 2023)
Background and Objectives: OSCE has been widely and increasingly used now-a-days. The OSCE is comprised of several stations; examinees are expected to perform a variety of clinical tasks within a specified time period. Performing a variety of clinical skills, in the laboratory there by evaluating competency of skills is possible. Investigator had conducted this study to assess the knowledge and expressed practice of nursing tutors before and after administration of Structured Teaching Programme on OSCE. And to find out the correlation between post-test knowledge and post-test expressed practice score on OSCE among nursing tutors of selected self-finance nursing colleges.Methods: A pre-experimental research design was used for this study. For data collection, structured tools were prepared which consists of three parts, first part deals with demographic data, second and third part includes structured quantitative questionnaire. Simple random sampling technique was used to select potential participants. Total 50 participants were selected with chit and lottery method for this study. Results:The study revealed that mean post-test knowledge score (14.1) was higher than mean pre-test knowledge score (7.52). The mean post-test expressed practice score (8.1) was higher than mean pre-test expressed practice score (3.56). There is an existence of a positive correlation (r =0.66) between knowledge and expressed Practice.Conclusion: The participants gained knowledge after delivering structured teaching about OSCE. There is positive co-relation between knowledge and expressed practice. So, it proves that structured teaching program is effective in imparting knowledge of OSCE.